2010
DOI: 10.1097/jto.0b013e3181d5e39e
|View full text |Cite
|
Sign up to set email alerts
|

A Dose Finding Study of Weekly and Every-3-Week nab-Paclitaxel Followed by Carboplatin as First-Line Therapy in Patients with Advanced Non-small Cell Lung Cancer

Abstract: Introduction: This nonrandomized study aimed to identify the optimal dose of every-3-week (q3w) and weekly nab-paclitaxel plus q3w carboplatin as first-line therapy in patients with advanced non-small cell lung cancer (NSCLC) for a phase 3 trial. Methods: Previously untreated patients with advanced NSCLC enrolled sequentially into seven cohorts (25 patients/cohort, N ϭ 175). Cohorts 1 to 4 and 5 to 7 received nab-paclitaxel q3w and weekly, respectively. Patients were evaluated for efficacy and safety. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 20 publications
(21 reference statements)
7
55
0
Order By: Relevance
“…60 No substantial pharmacokinetic interactions were noticed in the study with the combination. Among the 18 evaluable patients, ORR of 38.9% was reported with toxicity profile similar to the ones reported by Socinski et al 59 A combination of nab-paclitaxel 300 mg/m 2 , carboplatin AUC 6, and bevacizumab 15 mg/kg every 21 days was investigated in a Phase II setting by Reynolds et al as front line treatment of advanced (stage IIIB, IV) non-squamous NSCLC. 61 This study enrolled a total of 50 patients and a response rate of 31% and stable disease rate of 54%.…”
Section: Phase Ib/ii Studiessupporting
confidence: 60%
See 2 more Smart Citations
“…60 No substantial pharmacokinetic interactions were noticed in the study with the combination. Among the 18 evaluable patients, ORR of 38.9% was reported with toxicity profile similar to the ones reported by Socinski et al 59 A combination of nab-paclitaxel 300 mg/m 2 , carboplatin AUC 6, and bevacizumab 15 mg/kg every 21 days was investigated in a Phase II setting by Reynolds et al as front line treatment of advanced (stage IIIB, IV) non-squamous NSCLC. 61 This study enrolled a total of 50 patients and a response rate of 31% and stable disease rate of 54%.…”
Section: Phase Ib/ii Studiessupporting
confidence: 60%
“…Febrile neutropenia rate of 10% was also higher than the 5% reported in carboplatin/sb-paclitaxel/ bevacizumab group in Eastern Cooperative Oncology Group 4599 (ECOG 4599) study, 62 and 0% in carboplatin/nab-paclitaxel in Socinski's Phase I study. Somewhat counterintuitively, the incidence of grade 3 or 4 peripheral neuropathy or thrombocytopenia was only 4% and 10%, respectively, much lower in comparison to the corresponding non-bevacizumab cohort reported by Socinski et al 59 treated with otherwise the same dose schedule (see Table 2). Specific outcomes in the elderly population were not reported in this study wherein median age of participants was 67 years.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…In several trials, nab-paclitaxel-carboplatin demonstrated antitumour activity 12,50,51 . A phase i/ii study of nab-paclitaxel-carboplatin identified the maximum tolerated dose of single-agent nab-paclitaxel as 125 mg/m 2 administered in the first 3 weeks of a 4-week cycle 51 .…”
Section: A New Taxane For the Treatment Of Nsclcmentioning
confidence: 99%
“…More recently, a phase III clinical trial on MBC patients was conducted where 260 mg/ m 2 nap-paclitaxel was applied every week compared to 175 mg/ m 2 of paclitaxel every 3 week, and was found to show significant improvement in outcomes including overall response rate (ORR), time of tumor progression (TTP) and progression free survival (PFS) [11,53]. According to this data, nab-paclitaxel dose of 260 mg/ m 2 every 3 week has obtained an approval for use in MBC in more than 40 countries [54,55]. Furthermore, nab-paclitaxel has been shown to reduce drug exposure to healthy tissue [43].…”
Section: Dosage Bioavailability and Therapeutic Index In Mbcmentioning
confidence: 99%